THE ESTABLISHMENT OF THE SAMARKAND CUSTOMS OFFICE: ECONOMIC INTEGRATION AND IMPERIAL POLICY IN TURKESTAN (The Conference Hub, 2025)
This study explores the establishment and evolution of the customs system in the Turkestan region under the Russian Empire, with a particular focus on the opening of the Samarkand customs office in 1902. The customs office played a crucial role in formalizing trade processes, centralizing economic control, and integrating Turkestan into the broader economic space of the empire. By regulating imports and exports, especially of key commodities like tea, cotton, silk, and leather, the customs administration facilitated the growth of state revenues and contributed to the economic stabilization of the region. The gradual implementation of imperial customs policies reflects a broader socio-economic strategy aimed at strengthening Russia’s influence in Central Asia. The transformation from fragmented local customs practices to a unified imperial system marked a significant shift in regional trade dynamics and economic relations. Ultimately, the Samarkand customs office became a pivotal institution that reshaped both the local economy and the wider Central Asian market under Russian rule.